A smooth grid connection strategy for compressed air energy storage based on adaptive PI control - Wang, Dajiang; Sun, Yaxin; Ge, Yaming; Li, Jie; Yan, Chaoyang; Meng, Jianhui (Frontiers in Energy Research, 2024)
In the context of the application of compressed air energy storage system participating in power grid regulation, a large capacity of compressed air energy storage accessed to or off from the power grid will bring instability to the system, and there will be voltage and current impact during off-grid operation, which will pose a threat to system security. Therefore, this paper puts forward the control strategy of compressed air energy storage for both grid-connected and off-grid, and proposes a smooth grid-connected strategy of compressed air energy storage based on adaptive PI control, which can better improve the problem of excessive impulse current during the connection of compressed air energy storage. Finally, a simulation model is built in MATLAB/Simulink to verify the effectiveness and superiority of the proposed control strategy.